Capital cultural e sucesso escolar de alunos cegos - Soster, Lia Mara (2023)
The research analyzed the importance of culture, cultural capital, social interaction and language produced in the family relationships of blind people, seeking to understand how they act on their learning and their development. The motivation to undertake the research was closely related to the professional performance in front of pedagogical support in the care of people with visual impairment and interactions with blind students and their families. The objective was to analyze the relationship between the cultural capital arising from the family of blind students and the school success achieved by them. Therefore, the research sought to understand the theme of cultural capital, in front of formal educational processes, of blind students, in order to discuss, before the debate that turns to the educational processes of blind, an element of sociocultural order. Therefore, we performed an analysis of Educational Policies focused on Special Education, with a view to the demands of visual impairment; as well as identified the procedures adopted in school institutions, focused on the teaching and learning processes of the blind student, in order to understand the set of provisions that act on the blind person and that make it possible to abstract the structuring structures that can allow, through a given cultural capital, to achieve school success, especially those arising from the family of the blind student. In this context, interviews were conducted through an observation protocol, applied to the three selected families and to teachers of the state education network, who serve blind students. For this, the methodological procedures adopted combine bibliographic research with field research, through the analysis of an observation protocol. The research is based on a sociological approach, based on Bourdieusian theory, with a theoretical framework that made it possible to analyze the family-blind student imbrication. Authors such as Bourdieu (2013) and Passeron (2014) contributed, by providing a sociological thinking about disability, from the perspective of the habitus and cultural capital that involves educational processes, whether in the school, family and social relations, authors such as Amiralian (2017), Bruno (1997), Lemos (2000), Lima (2007), Motta (2018), Vigotski (2019), Viralonga (2013), studies related to visual impairment, are based, the specificities that involve the teaching and learning process and their interfaces with Education, as well as Arroyo (1997), Bueno (2004) and Lahire (1997) enabled an analysis of school failure/success through a cultural perspective. The analyzes directed to the understanding that the familiar habitus has a central role for the school success of blind students, because the families that adopted, in their relations, practices that encouraged autonomy and independence in the personal care of their child, who practices unfolded in autonomy and independence in the processes of schooling and socialization, obtaining, as a result, their school success. In line with inclusive practices, developed between school, family, Specialized Educational Service and Basic Education, blind students can achieve school success.